2021
DOI: 10.1002/onco.13893
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival of Combined Hepatocellular-Cholangiocarcinoma: A Nationwide Study

Abstract: Background. Combined hepatocellular-cholangiocarcinoma (HCC-CC) is an aggressive primary liver cancer. However, the clinical features are not clearly understood due to limited literature and the complex nature of both hepatocellular carcinoma (HCC) and cholangiocarcinoma (CC). Methods. The records of 100,754 patients with newly diagnosed liver cancer between 2004 and 2013 were obtained from the Taiwan Cancer Registry. The primary outcome measures were overall survival and local recurrence-free survival. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(32 reference statements)
2
6
0
Order By: Relevance
“…In our study, the clinicopathological features of cHCC-CCA were more similar to those of patients suffering from HCC infected with HBV (hepatitis B virus), both of which are associated with elevated AFP levels in most patients. The results of this study are consistent with those of previous studies ( 15 , 21 ). In clinical settings, cHCC-CCA is often misdiagnosed as either HCC or iCCA via imaging or hematology tests due to non-specific clinical manifestations, and a confirmed diagnosis of cHCC-CCA usually requires surgical resection ( 22 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our study, the clinicopathological features of cHCC-CCA were more similar to those of patients suffering from HCC infected with HBV (hepatitis B virus), both of which are associated with elevated AFP levels in most patients. The results of this study are consistent with those of previous studies ( 15 , 21 ). In clinical settings, cHCC-CCA is often misdiagnosed as either HCC or iCCA via imaging or hematology tests due to non-specific clinical manifestations, and a confirmed diagnosis of cHCC-CCA usually requires surgical resection ( 22 ).…”
Section: Discussionsupporting
confidence: 94%
“…Although cHCC-CCA has features of both HCC and CC, several studies have observed that cHCC-CCA shares more etiological features with HCC than with iCCA, especially with respect to its epithelial characteristics ( 5 , 15 ). In our study, the clinicopathological features of cHCC-CCA were more similar to those of patients suffering from HCC infected with HBV (hepatitis B virus), both of which are associated with elevated AFP levels in most patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TACE is a common adjuvant therapy after HCC, and previous studies have shown that TACE prolongs OS and RFS in HCC patients[ 35 ], which is based on the rationale of hindering the rich blood supply of HCC, thus promoting tumor necrosis[ 36 ]. TACE treatment has also been linked to improved survival in patients with cHCC-CCA following radical surgery, according to recent researches[ 24 , 25 ]. Studies including patients with unresectable cHCC-CCA have also shown that cHCC-CCA lesions with a rich blood supply have a higher response rate and better treatment outcomes for TACE[ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its molecular profile and genetic similarities, it is frequently considered a distinct form of cholangiocarcinoma,9 10 and it is often treated according to biliary tract cancer guidelines 11. In contrast, findings from a substantial cohort study using the Taiwan national Cancer Registry have demonstrated that managing this condition as HCC leads to more favourable treatment results, underscoring the distinctive complexities associated with CHC 12…”
Section: Introductionmentioning
confidence: 99%